2022
DOI: 10.1126/sciadv.abp9153
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of pre-mRNA structure by hnRNP proteins regulates alternative splicing of MALT1

Abstract: Alternative splicing plays key roles for cell type–specific regulation of protein function. It is controlled by cis-regulatory RNA elements that are recognized by RNA binding proteins (RBPs). The MALT1 paracaspase is a key factor of signaling pathways that mediate innate and adaptive immune responses. Alternative splicing of MALT1 is critical for controlling optimal T cell activation. We demonstrate that MALT1 splicing depends on RNA structural elements that sequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 73 publications
3
22
0
Order By: Relevance
“…Overall, our data correlates with previously reported measurements for hnRNP U-RNA interactions. These measurements include an observed 480 nM affinity for a dsRNA ligand measured by microscale thermophoresis, 47 2600 nM affinity for a 935-nt fragment of the Xist lncRNA measured by EMSA, 15 20-30 nM for a set of fragments of the MALT1 mRNA 24 and affinities ranging from 250 nM to >20 μM for a diverse panel of RNAs, as measured by EMSA. 9 Although most of these studies did not report Hill coefficients, the interaction between a C-terminal fragment of hnRNP U and a fragment of Xist RNA exhibited a Hill coefficient of 1.1, 15 comparable to our observed values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, our data correlates with previously reported measurements for hnRNP U-RNA interactions. These measurements include an observed 480 nM affinity for a dsRNA ligand measured by microscale thermophoresis, 47 2600 nM affinity for a 935-nt fragment of the Xist lncRNA measured by EMSA, 15 20-30 nM for a set of fragments of the MALT1 mRNA 24 and affinities ranging from 250 nM to >20 μM for a diverse panel of RNAs, as measured by EMSA. 9 Although most of these studies did not report Hill coefficients, the interaction between a C-terminal fragment of hnRNP U and a fragment of Xist RNA exhibited a Hill coefficient of 1.1, 15 comparable to our observed values.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a study of the role of hnRNP U and hnRNP L in alternative splicing of MALT1 pre-mRNA found that hnRNP U associates with GU-containing hairpins within the message and stabilizes secondary structure. 24…”
Section: Introductionmentioning
confidence: 99%
“…(iii) RNA-binding proteins can be an integral part of an RNA-protein complex and interact 'strongly' with the RNA components or are transiently associated, which also influences the crosslinking yield. (iv) The accessibility of protein residues for crosslinking, which may favor intrinsi-Nucleic Acids Research, 2022 17 cally disordered regions that are more solvent-exposed and make more transient contacts with the RNA, but also secondary structures of RNA, which reduce accessibility for crosslinking and can be modulated by RBP binding, may vary (78)(79)(80)(81). (v) Some RNA-binding regions might be involved in protein interaction rather than RNA interaction, as it has been shown for the U2AF (U2 auxiliary factor) Homology Motif (UHM) / UHM Ligand Motif (ULM) interactions (82)(83)(84).…”
Section: Discussionmentioning
confidence: 99%
“…As the nuclear target of extracellular signal‐regulated kinase (ERK), hnRNP K is indispensable for T‐cell late activation and IL‐2 production possibly by affecting transcription factors including nuclear factor (NF)‐kappa B and nuclear factor of activated T cells (NFAT) and protecting Vav1 from proteolysis (Chang et al, 2009). By controlling the alternative splicing of mucosa‐associated lymphoid tissue protein 1 (MALT1), hnRNP U, and hnRNP L antagonistically regulated T‐cell activation (Jones et al, 2022; Meininger et al, 2016). Instead, hnRNP A1 reinforces the stability of forkhead box P3 (FOXP3) and facilitates the differentiation from naive CD4 + T cells into regulatory T cells (Tregs) and the suppressive ability of Tregs (Xu Liu, Lin, et al, 2021).…”
Section: Hnrnps Regulate Gene Expressions Contributing To Inflammatio...mentioning
confidence: 99%
“…The effect of hnRNPs on transcription is exemplified by their associations with positive transcription elongation factor b (p‐TEFb) components, including cyclin‐dependent kinase 9 (CDK9), hexamethylene bis‐acetamide‐inducible protein (HEXIM), cyclin subunits, and 7SK RNA, that fine‐tune transcriptional elongation (Giraud et al, 2014). In terms of post‐transcriptional regulation, quite a few hnRNPs are implicated in exon inclusion or skipping among other alternative RNA splicing events (Chang et al, 2015; Jones et al, 2022; Meininger et al, 2016; Oberdoerffer et al, 2008; Paraboschi et al, 2014; Wu et al, 2010). The cooperation between hnRNP A2/B1 and DiGeorge Syndrome Critical Region Gene 8 (DGCR8), a key component of the microprocessor complex, facilitates the processing of primary microRNAs (pri‐miRNAs) into pre‐miRNA, where hnRNP A2/B1 also serves as an N6‐methyladenosine (m6A) reader by binding to a set of pri‐miRNA transcripts (Alarcón et al, 2015).…”
Section: Introductionmentioning
confidence: 99%